Práticas discursivas de educadores sociais junto a adolescentes em situação de vulnerabilidade social e/ou em cumprimento de medidas socioeducativas - Mata, Andréia Aparecida da (2016)
The research sought to understand the discursive practices of social educators with adolescents in situation vulnerable and / or fulfillment of educational measures. The participants were 05 educators of both sexes who work with adolescents in an institution located in the metropolitan region of Curitiba who participated in semi-structured interview. For data analysis was used the perspective of discursive practices of social constructionism, which aligns the Community Social Psychology. The results show that the social educator interviewed is the stability provided by a public employment, interest in acting as a teacher, have identification in working with adolescents and be familiar with the subject, the main reasons for the professional choice. The meanings of adolescence and adolescent denote a stereotypical view, but the contact with young people provided the review in this posture. The teacher does not have clarity of its role, like the work which is understood as a school, flexible, has little or no knowledge about the Sinase and socioeducaitivas measures. ECA stands in speech, however it brings inconsistency in relation to legislation and the role of the educator. The data reinforce the importance of the figure of the teacher as someone who can mediate adolescent care, though with a knowledge of praxis. From the data we can map out a direction for teacher training, taking into account especially the informal and non-formal education. However new research are suggested to understand how important the educator to other professionals and the need for discussion spaces among educators so that these issues can be discussed and aligned with the perspective of socio-educational.